2014
DOI: 10.1021/la500622f
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Trans Double Bond in Skin Barrier Sphingolipids: Permeability and Infrared Spectroscopic Study of Model Ceramide and Dihydroceramide Membranes

Abstract: Dihydroceramides (dCer) are members of the sphingolipid family that lack the C4 trans double bond in their sphingoid backbone. In addition to being precursors of ceramides (Cer) and phytoceramides, dCer have also been found in the extracellular lipid membranes of the epidermal barrier, the stratum corneum. However, their role in barrier homeostasis is not known. We studied how the lack of the trans double bond in dCer compared to Cer influences the permeability, lipid chain order, and packing of multilamellar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 60 publications
4
23
0
Order By: Relevance
“…Lipid mixtures with Cer NdS disordered at a higher temperature than those with Cer NS, consistent with the higher melting point of Cer NdS over Cer NS and previous results describing the formation of more thermally stable ordered domains of Cer NdS than Cer NS [ 8 , 17 , 38 ]. α-Hydroxylation of Cer NdS increased the lipid chain order at low temperatures and increased the main transition temperatures without any marked differences between ( R ) and ( S ) isomers ( Figure 3 E–G).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Lipid mixtures with Cer NdS disordered at a higher temperature than those with Cer NS, consistent with the higher melting point of Cer NdS over Cer NS and previous results describing the formation of more thermally stable ordered domains of Cer NdS than Cer NS [ 8 , 17 , 38 ]. α-Hydroxylation of Cer NdS increased the lipid chain order at low temperatures and increased the main transition temperatures without any marked differences between ( R ) and ( S ) isomers ( Figure 3 E–G).…”
Section: Resultssupporting
confidence: 89%
“…The behavior of skin-identical Cers with very long non-hydroxylated acyl chains has been widely explored in model biological membranes. The absence of a trans -double bond in Cer precursors, dihydroceramides, that form approximately 12% of Cers in healthy SC [ 7 ] did not affect the permeability of skin lipid models [ 8 ]. The shortening of the acyl or sphingoid chain in canonical sphingosine-based Cers decreased their barrier properties [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…8−10 However, a direct comparison suggested that the presence of the trans double bond in Cer is not essential to their barrier function: the permeability of model SC lipid membranes containing nonhydroxy acyl species of dihydroCer (Cer[NDS24] 11 ) or Cer (Cer[NS24]) was either comparable or only slightly greater in the membranes containing Cer[NDS24]. 12 The barrier properties of sphingolipids are also markedly influenced by their acyl chain length. According to the Cer synthase involved in their formation, the Cer acyls vary from long (13−19 carbons) to very long (20−26 carbons) to ultralong (>28 carbons).…”
Section: ■ Introductionmentioning
confidence: 99%
“…We have previously reported that the both acyl 12 and sphingosine chains shortening 13 , saturation of trans-double bond 71 , hydroxylations in C-4 8,72 or C-6 position 9,10 have different effects on the phase behavior and permeabilities of model skin lipid mixtures. Here we focused on the essential molecular features common to all Cer subclasses, hydroxyls at C-1 and C-3 and amide bond.…”
Section: Discussionmentioning
confidence: 99%